Vegetable and Fruits Consumption and Body Mass Index Among Farmers in Rural Areas of Indonesia: A Secondary Data Analysis - Rhosani, Nur Oktavia; Susanto, Tantut; Rasni, Hanny; Ma’fuah, Siti; Kurdi, Fahruddin (Al-Hijrah Indonesia, 2023)
Consumption of less vegetables and fruits in a person risks for overweight and obese. Farmers are one job with a low risk of consuming vegetables and fruit (< 250 grams) in one day. The purpose of this research was to know the association between the consumption of vegetable and fruits and body mass index among farmers in Posts of Non-Communicable Diseases (Posbindu PTM) Jenggawah Public Health Center, Jember Regency. A retrospective case-control study was used to analyze secondary data of Posbindu PTM registered from September to November 2020 among 81 farmers. The characteristics of participants, vegetable and fruit consumption, and body mass index were measured through KMS Posbindu PTM. There was a relationship between the consumption of vegetable and fruit with body mass index among farmers (p-value = 0.006; χ2= 8.725). Among 81 farmers were identified 59.3% less consumption of vegetables and fruit per day and 53,1% of obese. Farmers who consume less vegetables and fruit have a four times greater risk of being obese (OR= 4.00; 95% C = 1.562 – 10.242). Consumption vegetable and fruit is correlated with body mass index among farmers. Therefore, consuming vegetables and fruits should be improved to reduce the risk of obesity among farmers.